2006
DOI: 10.1027/0269-8803.20.3.170
|View full text |Cite
|
Sign up to set email alerts
|

An Event-Related Potential Investigation of Varieties of Negative Priming

Abstract: In an event-related potential (ERP) study of varieties of negative priming (NP), 20 participants performed two basic tasks, identification and localization. NP was established in response times (RTs) for two different conditions employed in the literature, DT (distractor-target shifts between subsequent displays), and DTTD (distractor-target reversals). With identification, there were two findings specific to DTTD: reduced amplitude of frontocentral P200 and earlier onset of response-locked lateralized readine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 35 publications
6
46
3
Order By: Relevance
“…For instance, the parietal P1-N1 and the P3 amplitude (Kathmann et al, 2006) were found to be diminished in the IR relative to the control condition. In contrast, relative to control trials the posterior N2 amplitude was found to be enhanced in IR trials (Gibbons, 2006;Ruge & Naumann, 2006). However, differences in early sensory components have not always been found in identity NP tasks (Gibbons, 2006;Gibbons et al, 2006).…”
Section: What Are the Neural And Electrophysiological Correlates Of Np?mentioning
confidence: 64%
See 2 more Smart Citations
“…For instance, the parietal P1-N1 and the P3 amplitude (Kathmann et al, 2006) were found to be diminished in the IR relative to the control condition. In contrast, relative to control trials the posterior N2 amplitude was found to be enhanced in IR trials (Gibbons, 2006;Ruge & Naumann, 2006). However, differences in early sensory components have not always been found in identity NP tasks (Gibbons, 2006;Gibbons et al, 2006).…”
Section: What Are the Neural And Electrophysiological Correlates Of Np?mentioning
confidence: 64%
“…In contrast, relative to control trials the posterior N2 amplitude was found to be enhanced in IR trials (Gibbons, 2006;Ruge & Naumann, 2006). However, differences in early sensory components have not always been found in identity NP tasks (Gibbons, 2006;Gibbons et al, 2006). In lexical-decision tasks, a reduced N400 amplitude has been observed when comparing both the IR condition and the semantic IR condition to the control condition (Heil & Rolke, 2004;Wagner, Baving, Berg, Cohen & Rockstroh, 2006).…”
Section: What Are the Neural And Electrophysiological Correlates Of Np?mentioning
confidence: 73%
See 1 more Smart Citation
“…The recording and analysis of ERPs is the preferred technique here as ERP allows to track, with a millisecond time-resolution, specific neural events related to inhibitory processes (Olofsson et al, 2008). With regard to the neural mechanisms, several specific components related to affective priming were examined in previous study, with the P1 component used as a marker of early, rapid processing of spatial stimuli; the N1 component reflected the attentional focus on target and a discrimination process within the focus of attention; P3 component reflected additional resources needed when the probe targets were still inhibited or updating of object-representations when objects were repeated (Kathmann et al, 2006;Taylor, 2002;Gibbons, 2006). In negative priming experiments, a smaller N1 amplitude was found.…”
Section: Introductionmentioning
confidence: 99%
“…This finding can be exclusively explained by assuming distractor location inhibition or the retrieval of inconsistent prime episode information attached to the previous distractor location. What is more, feature mismatching is frequently regarded to be an irrelevant or, at most, a very subordinate factor in visuospatial negative priming, which is indicated by the fact that many recent visuospatial priming studies have not even excluded or controlled feature mismatching as an explanation of their spatial priming effects (Buckolz, Avramidis, & Fitzgeorge, 2008;Buckolz et al, 2004;Gibbons, 2006;Guy & Buckolz, 2007;Guy, Buckolz, & Khan, 2006;Guy, Buckolz, & Pratt, 2004). It has been assumed that a process that detects mismatching features between the current probe target and the previous prime distractor object comes into play only under very specific circumstances that have not been investigated thoroughly Tipper et al, 1995).…”
mentioning
confidence: 99%